IMPROVING THE ACCOUNTING OF REAL ESTATE ASSETS (World Economics and Finance Bulletin, 2025)
The article examines issues related to the accounting of real estate assets. It highlights the use of International Financial Reporting Standards (IFRS) in organizing accounting processes for real estate.
Keywords: Real estate; property valuation; fair value